Conversion rate and the probable factors for conversion from laparoscopic to open cholecystectomy - Muhammed, Balen Salahaddin; Muhammed Dewana, Azhy; Saeed Ahmed, Baderkhan (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: In western countries, the incidence of Cholelithiasis is found to be more than 10% in general populations. After performing the first successful laparoscopic cholecystectomy (L.C.) in Germany by Muhe in 1986, it rapidly became the procedure of choice in treating symptomatic gall stone. L.C. has a lot of advantages, including minimal trauma, rapid recovery, less analgesic requirement with a good esthetic outcome, however even in the hands of a best surgeon still there is a small percentage of conversion to open laparotomy, some risk factors has been recognized as a reason for the conversion to open laparotomy. This study aims to evaluate the rate with the underlying risk factors that increase the chance of conversion to open cholecystectomy. Methods: A total of 1400 patients for whom L.C. was attempted, 54 were enrolled in this prospective study from January 2014 to January 2020. The exclusion criteria were malignancy or existence of gallbladder polyps detected pathologically. Patient demographics, indications for cholecystectomy, concomitant diseases, and histories of previous abdominal surgery were collected. The rates of conversion to open cholecystectomy with the underlying reasons for conversion were analyzed. Results: The overall rate of conversion to open cholecystectomy was 3.86% (54 patients). Out of 54 cases nearly two-thirds (61.1%) of the patients (33) were males and 38.9% of the patients (21) were females. Male: female ratio is 1.57:1. In the study sample, the conversion rate among obese (14/54) patients was 25.9% compared with the rate of 74.1% among non-obese (40/54) patients. Out of 3.86% of the conversion rate, 2.86% were non-obese and 1% were obese patients. The commonest etiology for conversion was thickened gall bladder due to severe gall bladder inflammation with fibrosis (21 patients) 38.9% followed by Acute cholecystitis (8 patients) 14.8%, then fibrosis (7 patients) 13% with aberrant anatomy at the calot’s triangle (6 patients) 11.1%. Conclusion: A thickened gall bladder was found to be the commonest risk factor for conversion to open cholecystectomy, the conversion from L.C. to O.C. should not be regarded as a failure of the procedure or as a complication, rather it should be regarded as a prudent maneuver for achieving the desired objective namely safe removal of the gall bladder.